THE RELATIONSHIP BETWEEN READING LITERACY AND NUMERACY IN SOLVING STORY PROBLEMS: ELEMENTARY SCHOOL STUDENTS - Pratiwi, Cerianing Putri; Murtafiah, Wasilatul; Rakhmad, Rakhmad (JURNAL EDUSCIENCE, 2025)
Purpose – This research aims to analyze the relationship between reading literacy and numeracy on elementary school students' ability to solve word problems.Methodology – This research uses a quantitative approach with a correlational design and data analysis techniques in the form of multiple linear regression. The research population consists of elementary school students, with a sample of 102 students randomly selected from several classes. The research instruments include three types of tests: reading literacy, numeracy, and word problem-solving. The normality test is conducted using the Kolmogorov-Smirnov test to ensure normal data distribution, followed by the Pearson correlation test to determine the strength of the relationship between variables, and the regression analysis to determine the simultaneous correlation of the two independent variables with the dependent variable.Findings – The research results show a significant relationship between reading literacy and the ability to solve word problems (r = 0.896) and between numeracy and the ability to solve word problems (r = 0.902). Regression analysis shows that both independent variables explain 87.4% of the variation in students' ability to solve word problems. These findings emphasize the importance of strengthening reading and numeracy literacy in an integrated manner in contextual mathematics learning. This indicates that students' success in solving word problems relies not only on arithmetic skills but also on their understanding of the content of the reading.Contribution – This study recommends developing an integrated learning model combining language literacy and numeracy aspects to comprehensively enhance students' problem-solving skills at the elementary school level. This research contributes to developing integrated learning strategies that incorporate reading literacy and numeracy skills to improve students' problem-solving competencies in elementary schools.